ANALISIS STRATEGI TRANSFORMASI DIGITAL MELALUI PENDEKATAN SWOT BERBASIS PEMBOBOTAN PADA RAPOR PENDIDIKAN: STUDI KASUS DI SDN 005 SANGASANGA - Winaryati; Arie Ekayudhistira Kirana Tejawati; Friska Umi Puspita Sari; Syalma Faradila Nur; Irma; Nurlaili; Usfandi Haryaka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the strategic planning of digital transformation in education through a weighted SWOT analysis approach based on Education Report Card data at SDN 005 Sangasanga. The study was motivated by the limited use of data-based planning and the suboptimal implementation of digital learning in elementary schools. The objective of this research is to identify internal and external strategic factors, analyze the implementation of weighted SWOT analysis, and formulate priority strategies for improving digital learning quality. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation. The data analysis technique used the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings indicate that the implementation of strategic planning based on Education Report Card data has not been fully optimized. Major obstacles include limited technological infrastructure, low digital literacy among teachers, and inadequate integration of data into school planning. However, the school demonstrates strengths in leadership commitment, teacher collaboration, and institutional willingness to adapt to digital transformation. The weighted SWOT analysis revealed that strengthening teacher digital competence, improving infrastructure, and implementing participatory data-driven planning are the main strategic priorities. The study concludes that data-based strategic planning integrated with weighted SWOT analysis can support more adaptive, measurable, and sustainable school management in the digital era.